PENGEMBANGAN PENDIDIKAN BUDAYA DAN KARAKTER BANGSA DALAM UPAYA MENGHADAPI TANTANGAN GLOBAL - Armai Arief (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2014)
Building nation’s characters is an interesting issue to discuss. The issue cannot be separated from other issues within the nation. In this case, education plays a significant role. Education has to be able to lead the nation to solve various problems, including the changing values and its implication. It is important to note how education can contribute to the process of revitalization of cultural values within the context of social changes. Indonesian education is very fortunate to have Pancasila as its basic principle. Actualization of the values of Pancasila can be seen as a promising alternative in developing nation’s characters and culture. Pancasila is the core of national philosophy and ideology that has been formulated based on Indonesia’s culture and religions. It is important to note that the spirit of Pancasila is manifest in the formulation of the objectives of the national education. DOI: 10.15408/tjems.v1i2.1269